Habitat type and environmental conditions influence the age and growth of a temperate marine damselfish - Williams, Chelsea M.; Eagleton, Jacob L.; Pondella, Daniel J.; Claisse, Jeremy T. (Frontiers in Marine Science, 2022)
Life history parameters for fishes have generally been applied to species across their entire range, however, different ecological and environmental conditions and processes (e.g., sea surface temperature, habitat, primary productivity, fishing mortality, resource availability) influence life history patterns at smaller spatial scales. By focusing on a historically protected species, we determined how environmental and ecological factors shape patterns in growth and longevity, without the impact of fishing. The Garibaldi (Hypsypops rubicundus) is a territorial marine damselfish native to the shallow rocky reefs of southern California. Garibaldi were collected from five mainland locations and five Channel Islands throughout the Southern California Bight. Paired natural reef and artificial reef habitats (i.e., breakwaters and jetties) in each mainland location were sampled. Otolith-based ageing and biological data from these populations were used to assess how age and growth vary by location, reef type (natural/artificial), island or mainland, mean annual sea surface temperature, and/or sex. The annual formation of growth increments in otoliths was validated in-situ using tetracycline mark-recapture methods to confirm that increments are formed annually. Garibaldi grew significantly larger on artificial reefs than on natural reefs but tended to live longer on paired natural reefs. Regionally, growth and longevity followed mean annual sea surface temperature gradients, consistent with Bergmann’s rule. Garibaldi exhibited clear sexual size dimorphism; males grew larger, which is uncharacteristic for both damselfish and other marine fishes from the southern California. The Garibaldi collected for this study had a maximum age of 57 years, which makes this the longest lived damselfish species by two decades.